Application of epithermal neutron activiation analysis for the determination of indium and cadmium in blendes, interference of manganese - Cohen, Isaac Marcos (Elsevier Sequoia, 1973)
Fil: Cohen, Isaac Marcos Comisión Nacional de Energía Atómica; Argentina